Pulling Back the Shades : Erotica, Intimacy, and the Longings of a Woman's Heart - Gresh, Dannah, 1967-; Slattery, Julianna, 1969- (Chicago : Moody Publishers, 2014)
With solid Biblical teaching and transparent stories, trusted authors Dannah Gresh and Dr. Juli Slattery offer an unflinching look at the most personal questions women ask. The book offers practical advice for women to address five core longings: to be cherished by a man, to be protected by a strong man, to rescue a man, to be sexually alive, to escape reality. God designed women with these longings and has a plan to satisfy them. It's time for women to identify their intimate longings and God-honoring ways to fulfill them.
Includes bibliographical references.
Keywords: Sex -- Religious aspects -- Christianity; Christian women -- Sexual behavior; Christian women -- Religious life